Study on the Extraction of Rare Earth Elements (REEs) from Phosphogypsum Using Gluconobacter oxydans Culture Solution - Jiangang Zhang; Zhuo Qi; Zijian He; Xinyue Zhang; Qinglian Zhang; Xiangdong Su (Molecules)
With the rapid development of modern industry, particularly in the fields of electric vehicles and renewable energy technologies, the demand for rare earth elements (REEs) has surged dramatically. Phosphogypsum (PG), which is an industrial waste product generated during the production of phosphoric acid through the sulfuric acid process, is rich in REEs. However, traditional chemical leaching methods pose environmental pollution and resource wastage issues. This study aims to explore the feasibility and optimal conditions for bioleaching REEs from phosphogypsum using Gluconobacter oxydans (G. oxydans). The phase composition and components of phosphogypsum, as well as the growth characteristics and leaching efficiency of G. oxydans, were analyzed in detail using SEM, EDS, XRD, and XRF techniques. Experimental results indicate that G. oxydans can effectively leach REEs from phosphogypsum under conditions of 28 °C, an agitation speed of 150 rpm, and a liquid-to-solid ratio of 4:1, with a maximum leaching efficiency of 24.67%. Moreover, it is revealed in the study that G. oxydans exhibits selectivity in leaching REEs. Specifically, the leaching efficiency for Nd is significantly enhanced at low pH values. This research provides a theoretical basis and practical application example for the efficient and environmentally friendly recovery of REEs from phosphogypsum.